2022
DOI: 10.2196/40765
|View full text |Cite
|
Sign up to set email alerts
|

Recruitment and Retention in Remote Research: Learnings From a Large, Decentralized Real-world Study

Abstract: Background Smartphones are increasingly used in health research. They provide a continuous connection between participants and researchers to monitor long-term health trajectories of large populations at a fraction of the cost of traditional research studies. However, despite the potential of using smartphones in remote research, there is an urgent need to develop effective strategies to reach, recruit, and retain the target populations in a representative and equitable manner. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 72 publications
1
10
0
Order By: Relevance
“…An evaluation of 24 traditional trials conducted by the National Drug Abuse Treatment Clinical Trials Network demonstrated no statistical differences in retention across racial and ethnic groups [ 17 ]. However, a more recent analysis of retention in a decentralized study demonstrated higher retention of non-Hispanic whites as compared to Black and Hispanic participants [ 18 ] consistent with our study’s findings. Taken together, this emerging literature regarding participant engagement and retention in decentralized studies suggests the need to develop and test targeted strategies to promote engagement and retention of minority study participants.…”
Section: Discussionsupporting
confidence: 92%
“…An evaluation of 24 traditional trials conducted by the National Drug Abuse Treatment Clinical Trials Network demonstrated no statistical differences in retention across racial and ethnic groups [ 17 ]. However, a more recent analysis of retention in a decentralized study demonstrated higher retention of non-Hispanic whites as compared to Black and Hispanic participants [ 18 ] consistent with our study’s findings. Taken together, this emerging literature regarding participant engagement and retention in decentralized studies suggests the need to develop and test targeted strategies to promote engagement and retention of minority study participants.…”
Section: Discussionsupporting
confidence: 92%
“…This finding is consistent with several previous engagement studies. 21,45,46 This study also demonstrated the feasibility of collecting active and passive data streams for long-term behavior monitoring. While there is growing interest amongst researchers in gathering behavioral data without having to rely on episodic in-clinic assessments that may be subject to recall bias 47 , there is limited empirical research quantifying the long-term participant engagement differences between active (surveys) and passive data streams (smartphones and wearables).…”
Section: Variablesmentioning
confidence: 74%
“…The considerations comprehensively support the DCT design, as it enables study monitoring with little cost and can reflect real‐world clinical practices. In the same vein, DCT approaches have been observed in trials for atrial fibrillation, 12 Parkinson's disease, 29 and type 2 diabetes, 30 all of which satisfy the aforementioned features. The efficacy results in our study were comparable to those in the traditional clinical trial, suggesting the feasibility of a DCT design in functional constipation.…”
Section: Discussionmentioning
confidence: 91%
“…It is noteworthy that recruitment and data collection processes can be influenced by various unexpected factors, such as device heterogeneity 29 . Li et al 29 found that the device type of mobile phones (Android vs. iOS) substantially affected the data sharing patterns (e.g., providing barometer data) of participants in a study with 10,000 participants. In another study, the layout of the recruitment website influenced participant engagement and interest in the study 31 .…”
Section: Discussionmentioning
confidence: 99%